Effect of film thickness on the width of percolation threshold in metal-dielectric composites - Mokhtari, M.; Zekri, L.; Kaiss, A.; Zekri, N. (Condensed Matter Physics, 2016)
The effect of thickness on the width of the percolation threshold in metal-dielectric composite films was examined. The distribution of current intensities through cubic networks of metal and dielectric components
was determined using Kirchhoff’s equations. From the tail of current distribution, the width of the percolation
threshold was defined using Lévy statistics, and determined as a function of the film thickness for a system size
100. In the 2D-3D crossover region, the percolation width decreases as a power-law with a power exponent of
0.36±0.01. Дослiджено вплив товщини плiвки на ширину перколяцiйного порогу у плiвках метал-дiелектричних композитiв. Розподiл iнтенсивностей струму через кубiчнi мережi компонентiв металу i дiелектрика визначався, використовуючи рiвняння Кiргофа. Ширина перколяцiйного порогу визначалася з хвоста розподiлу струму, використовуючи статистику Левi, i була визначена як функцiя товщини плiвки для розмiру
системи 100. В кросовернiй областi 2D-3D ширина перколяцiї зменшується за степеневим законом з показником 0.36±0.01.